In Vitro Bioassay-Guided Identification of Anticancer Properties from Moringa oleifera Lam. Leaf against the MDA-MB-231 Cell Line - Prapakorn Wisitpongpun; Nungruthai Suphrom; Pachuen Potup; Nitra Nuengchamnong; Philip C. Calder; Kanchana Usuwanthim (MDPI AG, 2020)
Moringa oleifera Lam. (MO) is a medicinal plant distributed across the Middle East, Asia, and Africa. MO has been used in the traditional treatment of various diseases including cancer. This study aimed to perform bioassay-guided fractionation and identification of bioactive compounds from MO leaf against MDA-MB-231 breast cancer cells. MO leaf was sequentially extracted with hexane, ethyl acetate (EtOAc), and ethanol. The most effective extract was subjected to fractionation. MO extract and its derived fractions were continuously screened for anti-cancer activities. The strongest fraction was selected for re-fractionation and identification of bioactive compounds using LC-ESI-QTOF-MS/MS analysis. The best anticancer activities were related to the fraction no. 7-derived crude EtOAc extract. This fraction significantly reduced cell viability and clonogenic growth and increased cells apoptosis. Moreover, sub-fraction no. 7.7-derived fraction no. 7 was selected for the identification of bioactive compounds. There were 10 candidate compounds tentatively identified by LC-ESI-QTOF-MS. Three of identified compounds (7-octenoic acid, oleamide, and 1-phenyl-2-pentanol) showed anticancer activities by inducing cell cycle arrest and triggering apoptosis through suppressed Bcl-2 expression which subsequently promotes activation of caspase 3, indicators for the apoptosis pathway. This study identified 10 candidate compounds that may have potential in the field of anticancer substances.